Clinicopathological features and treatment outcomes of the rare, salivary duct carcinoma of parotid gland. Issue 1 (December 2016) - AL-Qahtani, Khalid; Tunio, Mutahir; Bayoumi, Yasser; Gurusamy, Venkada; Bahamdain, Fahad; Fatani, Hanadi
Abstract Background Salivary ductal carcinoma (SDC) of parotid gland is a rare and aggressive entity; accounting for 1–3 % of all malignant salivary gland tumors, 0.2 % of epithelial salivary gland neoplasms, 0.5 % of salivary gland carcinomas, and 1.1 % of parotid gland carcinomas. Here in we aimed to evaluate the clinico-pathological features and treatment outcomes of parotid gland SDC in Saudi population. Methods Among 38 patients with parotid malignancies, who were treated in two major tertiary care referral cancer centers between December 2007 and December 2014, seven cases (18.4 %) were found to have SDC, which were investigated for clinicopathological features, locoregional recurrences (LRRs), distant metastasis (DM) and survival rates. Results Mean age of cohort was 62.3 years (range: 41–83) and female predominant (71.4 %). All patients underwent total parotidectomy and ipsilateral neck dissection. Mean tumor size was 3.4 cm (range: 2.1–5.3); perineural invasion (85.8 %); lymph node involvement (42.9 %); and HER-2 neu overexpression (28.6 %). Postoperative radiation therapy (PORT) was given to six patients (dose: 50–66 Gy). Median follow-up was 20.2 months (range: 11–48). LRRs were seen in five (71.4 %) patients (base of skull, 3 patients; cervical nodes, one patient; parotid bed, one patient). LRRs were salvaged with resection (two patients) and re-irradiation (one patient with base of skull). DM in lungs was seen in three patients (42.8 %); one treated with carboplatin/paclitaxel based chemotherapy. The 4-year disease free and overall survival rates were 16.7 % and 40 % respectively. Conclusion SDC of parotid gland is a rare and aggressive entity, and most of LRRs were seen in the base of skull, which warrants inclusion of base of skull in clinical target volume in PORT planning. Role of anti HER-2 targeted therapy in SDC with HER-2 neu overexpression needs further investigations.